Influence of particle size on appearance and in vitro efficacy of sunscreens - Débora Granemann e Silva; Fernanda Daud Sarruf; Larissa Carolina Diniz de Oliveira; Elizabeth Pinheiro Gomes Arêas; Telma Mary Kaneko; Vladi Olga Consiglieri; Maria Valéria Robles Velasco; André Rolim Baby (Brazilian Journal of Pharmaceutical Sciences, 2013)
Nanotechnology applies to diverse sectors of science. In cosmetic area, investments have strengthened the idea that nanoproducts provide innumerable benefits to consumers. Extreme exposition to solar light can cause undesirable effects, thus, adding UV filters in cosmetic products are often used as prevention. Ethylhexyl methoxycinnamate and benzophenone-3 are UV filters widely used in sunscreen formulations, this UV filters absorb UVB and UVA radiation, respectively. In this study, sunscreen formulations were developed as nano and macroemulsion, but composed by the same raw material. Nanoemulsion was obtained by phase inversion temperature method (PIT). Physical and functional properties were evaluated by visual analysis, particle size distribution and by diffuse reflectance spectrophotometry. Achieved nanoemulsion showed bluish brightness aspect, less apparent consistency than macroemulsion, stability longer than 48 hours (22.0 ± 2.0 °C) and bimodal particle size distribution with average (mean) sizes around 10 nm (61%) and 4.5 µm (39%). Macroemulsion showed milky aspect, higher consistency than nanoemulsion, instability after 48 hours (22.0 ± 2.0 °C) and bimodal particle size distribution with average (mean) size around 202 nm (9%) and 10.4 µm (91%). Effectiveness profile of sunscreen formulations remained apparently similar, based on achieved results of in vitro SPF, UVA/UVB ratio and critical wavelength assays.